FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI PENCEGAHAN OSTEOPOROSIS - Lilik Sriwiyati; Octavereza Putri (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Background: Osteoporosis is characterized by a decrease in bone mass density and deterioration of bone microarchitecture, so that the bones become brittle and break easily. Efforts should be made to minimize the complications of osteoporosis by preventing osteoporosis. To do osteoporosis prevention requires good motivation. The purpose of this study was to analyze lifestyle as osteoporosis factor. Subjects of this research were Kadilangu villagers. The samples were 102 responden selected by using total sampling method. Method of the research is a corelational study. This research has two variables, the independent variable is factors that influence motivation (age, gender, education level, level of knowledge) and the dependent variable is the motivation to prevent osteoporosis. Collecting data use questionnaire paper. Data analysis use logistic regresion test with p=0,05. The result of this research is knowledge is the factor that affect on prevention motivation of osteoporosis, that is with value p = 0,000, OR 56,571 ; CI 95 % 4,094 until 297,099. Variable age, gender, dan education have no effect on prevention motivation of osteoporosis. Statistical test results of these variables are: age (p = 0,463), gender (p = 0,696, education (p = 0,671). The value of Nagelkerke R Square is 49,4 %. The conclusion of this study is that the factors that influence the motivation to prevent osteoporosis are the level of knowledge, while the age, gender, and level of education have no effect on preventing osteoporosis on villagers of Kadilangu, Baki, Sukoharjo. Keywords: age, education, gender, knowledge, motivation, osteoporosis